Da pesca ao natural: Trajetória do turismo em Mato Grosso do Sul (1970 a 2015) - Violin, Fábio Luciano [UNESP]; Alves, Gilberto Luiz (Editora de Livros IABS, 2017)
The object of analysis of this study is the trajectory of tourism in Mato Grosso do Sul State, between 1970 and 2015, with the main objectives of describing the historical course of tourism in the state and the triggers that changed the predominance of fishing activities to the offering of attractions linked to natural tourism. This work was developed with the use of secondary sources, institutional documents and archives, as well as on-site observations, photographic records and semi-structured interviews with tourists and residents. Public policies, combined with the investments of the private sector, were deemed responsible for substantially altering tourism characteristics in the State, including the nature of activities and the areas for its expansion. Ecotourism, representing a new stage of tourism in the State, is characterized by the support to commercial activities, with disregard for cultural singularities and the environment. The directed actions of the public sector, and the public and private investments in structure, have substantially altered the nature of tourist development in the state.
From fishing to natural: Trajectory of tourism in Mato Grosso do Sul (1970 to 2015)
Keywords: Ecotourism; Environment; Fishing tourism; Regional development